Multi-Vector Model Predictive Control for Three-Phase Four-Switch Rectifier with Capacitor Voltage Balancing - Baoge ZHANG; Weijie MA (Zhongguo dianli)
Three-phase four-switch rectifier has the problem of unbalanced capacitor voltage because one phase of its AC side is directly connected between two capacitor neutral points on the DC side. In order to ensure the capacitor voltage balance and further enhance the steady-state performance of the three-phase four-switch rectifier control system, a multi-vector model predictive control (MVMPC) strategy for capacitor voltage balance is proposed. Since no zero voltage vector for three-phase four-switch rectifier, the equivalent zero vector model is derived to implement the proposed control strategy. To ensure the stability of the DC voltage, it is proposed to power compensation strategy to balance the DC-link capacitor voltage. In multi-vector model predictive control, two basic voltage vectors and one equivalent zero vector are selected for each sampling period, which makes the amplitude of the equivalent synthetic vector direction adjustable, as a result of expanding the range of the equivalent synthetic vector and improving the system's control precision. The simulation results show that the multi-vector model predictive control with capacitor voltage balancing strategy can make the three-phase four-switch rectifier operate reliably and stably, with great control effects on power, grid side current, DC side capacitor voltage. Compared with the conventional model predictive control (CMPC) strategy, the proposed control strategy has less power ripple and lower current harmonic content with a constant switching frequency.